A comparative study of functional outcome between posterior lumbar fusion and posterior lumbar interbody fusion in spondylolisthesis - Singh, Harpreet; Patel, Dhruv; Tyagi, Sangam; Saoji, Krushna; Patel, Tilak; Patel, Parth (International Journal of Research in Orthopaedics, 2021)
Background: Spondylolisthesis is condition in which one vertebra slips over other vertebra. This study has been done to compare the functional outcome and complications of two techniques: posterior lumbar fusion (intertransverse fusion) and posterior lumbar interbody fusion. Methods: Total 20 patients with spondylolisthesis admitted in a tertiary care centre in Rajasthan were allotted alternatively in posterior lumbar fusion (PLF) group and posterior lumbar interbody fusion (PLIF) group. In PLF, fusion was done by placing bone graft between transverse processes and around facets. In PLIF, fusion was bone by placing cage in between vertebral bodies. Results: 20 patients were included in our study with female predominance (65%). Mean age was 54.2 years (PLF=58.4 and PLIF=50.2). 70% patients have L4-L5 level spondylolisthesis. Average operative time was less in PLF group, which is statistically significant. Functional outcome was measured by using visual analogue scale (VAS) score and Japanese orthopedics association score (JOAS) at 3 weeks, 3 months and 6 months. There is a significant decrease between preoperative VAS and at 6 months, in both PLF and PLIF group. JOAS was significantly increased at 6 months in both PLF and PLIF group as compared to preoperative score. But difference in JOAS at 6 months is not significant between PLF and PLIF. Conclusions: Both PLF and PLIF are equally effective for spondylolisthesis. Both techniques have same satisfactory results. As PLIF is more invasive technique, more operative time and more complications are seen.